KEDUDUKAN HAK MENDAHULU TAGIHAN PAJAK PADA PROSES KEPAILITAN (STUDI PUTUSAN-PUTUSAN PENGADILAN NIAGA) - Sheila Miranda Hasibuan; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Universitas Sumatera Utara, 2019)
ABSTRACT The main state revenue is through the tax sector. The issue of corporate bankruptcy which is an economic phenomenon that cannot be avoided in the business world. One of the effects of bankruptcy is the reduced state revenue from payment of corporate taxes. One important factor in the division of bankrupt assets is the position of creditors and the position of the state's right to payment of tax debts in the debtor's bankruptcy process. Another problem that might arise is that it turns out that the assets owned by the bankrupt debtor are insufficient to be used as repayment of the debts of the creditors. The portion of debt tax payable in some cases can exceed the proceeds of the sale of bankrupt assets, so that if all are prioritized to pay off the tax debt, the other creditors are threatened not to get anything from the proceeds of the sale of bankrupt assets. The problems discussed in this thesis are concerning the prior position of rights in the laws and regulations related to bankruptcy, collection of tax debts against taxpayers declared bankrupt and regarding the application of preceding rights to tax debts to taxpayers declared bankrupt based on court decisions. The research method used is normative juridical descriptive nature. This research focuses on library research and is based on secondary data, and analyzed using qualitative analysis methods. The research conducted shows the results that the laws and regulations governing the prior rights of creditors to debtor debts are insolvent spread in many laws, which causes legal uncertainty. This situation resulted in the position of the creditors becoming vague and uncertain. Furthermore, regarding taxpayers declared bankrupt, either the person or entity assigned to do the settlement is prohibited from distributing the assets of the taxpayer in bankruptcy, before using the asset to pay the tax debt of the taxpayer concerned. The application of prior rights over tax debts to taxpayers declared bankrupt based on court decisions has multiple interpretations, on the one hand recognizing the position of the state as the prior owner of the rights, but in other decisions the position of rights before the state is ruled out. Keywords: Priority Rights, Bankruptcy, Tax Bills